2023
DOI: 10.2147/ccid.s393841
|View full text |Cite
|
Sign up to set email alerts
|

Classic Eosinophilic Pustular Folliculitis in an Immunocompetent Patient with Syphilis: Are They Related?

Abstract: Eosinophilic pustular folliculitis (EPF) is a rare, chronic, non-infectious inflammatory skin disease. Although the pathogenesis of EPF is unknown, eosinophilic pustular folliculitis may be associated with human immunodeficiency virus (HIV) infection, malignancies or syphilis. Here, we report the first case of EPF associated with syphilis, indicating that syphilis and EPF are correlated with T-helper type 2 immune responses. A 48-year-old man gradually developed erythema and pustules on the face, neck. Physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The infantile type mostly occurs in children under one year old, with a higher prevalence in male infants, and 70% of patients develop symptoms within six months after birth. 5 , 6 The etiology and pathogenesis of this disease are not yet fully understood. It has been reported that EPF can be associated with human immunodeficiency virus, autoimmune diseases, and autologous peripheral blood stem cell and allogeneic bone marrow stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The infantile type mostly occurs in children under one year old, with a higher prevalence in male infants, and 70% of patients develop symptoms within six months after birth. 5 , 6 The etiology and pathogenesis of this disease are not yet fully understood. It has been reported that EPF can be associated with human immunodeficiency virus, autoimmune diseases, and autologous peripheral blood stem cell and allogeneic bone marrow stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The disease typically follows a chronic course and is more prevalent among young men. 2 The hallmark of a typical skin lesion is a whirlpool or creeping red patch, which eventually evolves into red, pinhead-sized follicular papules and pustules. 3 These lesions may be clustered or arranged circularly, displaying clear boundaries.…”
Section: Introductionmentioning
confidence: 99%